Clinicopathological Characteristics and Outcomes of Lupus Nephritis Patients With Thrombocytopenia: A Single‐Center Retrospective Study - Hui Diao; Yuting Fan; Di Kang; Zhiqing Chen; Yuewen Lu; Xiamin Huang; Xi Xia; Wei Chen (Immunity, Inflammation and Disease)
ABSTRACT Objectives The objective of this study is to analyze and summarize the clinical characteristics and prognosis of lupus nephritis (LN) patients with thrombocytopenia and to improve the cognition of the disease. Methods 896 LN patients were enrolled in this study and their clinical and pathological data were collected and analyzed. The primary end point was mortality. The secondary end point was adverse renal outcomes, defined as doubling of the baseline serum creatinine or end‐stage renal diseases. Cox regression model was used to analyze the risk factors of mortality or renal events in LN with and without thrombocytopenia. Results Among 896 LN patients, 70 (7.8%) were diagnosed with thrombocytopenia. LN patients with thrombocytopenia had lower estimated glomerular filtration rate (eGFR) and higher systemic lupus erythematosus disease activity index (SLE‐DAI), proportion of anemia, leukopenia, hypocomplementemia, and positive anti‐cardiolipin antibodies, compared to those without thrombocytopenia. LN patients with thrombocytopenia had higher scores of activity index and more activity features (endocapillary hypercellularity, medullary loop necrosis) on kidney biopsy. There was no significant difference in patient survival and renal survival between LN patients with and without thrombocytopenia. Anemia was a risk factor for death in LN patients with thrombocytopenia and lower eGFR was a risk factor for adverse renal outcomes. Conclusions LN patients with thrombocytopenia showed higher disease activity, more anti‐cardiolipin antibody positivity and a higher activity index in kidney biopsy, but the prognosis was similar compared with those without thrombocytopenia. Anemia was a risk factor for death in LN patients with thrombocytopenia.